Wheelchair Skills Training for Functional Activity in Adults with Cervical Spinal Cord Injury - Yeo, Sang Seok; Kwon, Jung Won (International Journal of Sports Medicine, 2018)
Wheelchair skills training can improve independent wheeled mobility for daily living activities as well as functional and social participation of adults with cervical spinal cord injury (C-SCI). The objective of this study was to examine the effectiveness of wheelchair skills training in improving both wheelchair skills and upper arm skilled performance in adults with C-SCI. In a randomized controlled study, 24 adults with tetraplegia were randomized and allocated to training group (n=13) or control group (n=11). The training group attended wheelchair skills training sessions, whereas the control group attended conventional exercise sessions. All interventions lasted 8 weeks, with a frequency of 3 days per week. All individuals were tested with the Wheelchair Skills Test (WST) and the Van Lieshout Test (VLT). The test was repeated at pre- and post-training (after 4 weeks and 8 weeks). For WST, univariate analysis demonstrated significant main effects in between-group, within-group, and group-by-time interaction (p<0.05). VLT showed no significant effect in between-group comparison (p>0.05), whereas within-group comparison of test times and group-by-time interaction showed significant main effects (p<0.05). Thus, wheelchair skills training is more beneficial for adults with C-SCI than conventional exercise.
Keywords: wheelchairs; mobility; upper extremity; motor skills; spinal cord injury